Islamic Values-Based Legal Counseling in Bullying Prevention: Penyuluhan Hukum Berbasis Nilai Islam dalam Pencegahan Bullying - Dasa Suryantoro, Dwi; Rofiq, Ainur (Al Busyro : Jurnal Pengabdian Kepada Masyarakat, 2025)
Bullying in the school environment is a serious problem that has an impact on mental health, social development, and academic achievement of students. In addition, bullying also has legal consequences that are often poorly understood by students and schools. The Community Service Program (PKM) aims to provide legal counseling to students of MTS Nurul Huda, Bajuran Village, Bondowoso Regency, so that they understand the forms of bullying, its impact, and its legal consequences. The activity was carried out on February 10, 2025 using a participatory approach through the delivery of interactive materials, group discussions, and case simulations. The results of the evaluation showed a significant increase in students' understanding of bullying from both moral, social, and juridical aspects. The participants showed high enthusiasm and realized the importance of creating a safe, inclusive, and violence-free school environment. In conclusion, this activity makes a positive contribution to bullying prevention efforts among madrasah students. As a recommendation, similar legal counseling can be developed in other educational institutions as a model in building legal awareness and realizing child-friendly schools.